2021
DOI: 10.3390/ijms22052460
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Amyloid and Tau Protein in Post-Ischemic Neurodegeneration of the Hippocampus of a Nature Identical to Alzheimer's Disease

Abstract: Recent evidence suggests that amyloid and tau protein are of vital importance in post-ischemic death of CA1 pyramidal neurons of the hippocampus. In this review, we summarize protein alterations associated with Alzheimer's disease and their gene expression (amyloid protein precursor and tau protein) after cerebral ischemia, as well as their roles in post-ischemic hippocampus neurodegeneration. In recent years, multiple studies aimed to elucidate the post-ischemic processes in the development of hippocampus neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 133 publications
4
36
0
Order By: Relevance
“…1A). Given that p-Tau217 is an early marker of neurodegeneration and Alzheimer's [20,27,28], these results are consistent with the role of phosphorylated Tau in HAND pathogenesis and suggest that increase in this factor may precede HAND diagnosis. Amyloidogenic proteins and amyloid peptides are associated with lipid rafts [29][30][31][32][33], and our previous study suggested that increased abundance of lipid rafts caused by Nef-containing extracellular vesicles (exNef) may be the reason for the upregulation of APP and Tau [11].…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…1A). Given that p-Tau217 is an early marker of neurodegeneration and Alzheimer's [20,27,28], these results are consistent with the role of phosphorylated Tau in HAND pathogenesis and suggest that increase in this factor may precede HAND diagnosis. Amyloidogenic proteins and amyloid peptides are associated with lipid rafts [29][30][31][32][33], and our previous study suggested that increased abundance of lipid rafts caused by Nef-containing extracellular vesicles (exNef) may be the reason for the upregulation of APP and Tau [11].…”
Section: Resultssupporting
confidence: 70%
“…1A). Given that p-Tau217 is an early marker of neurodegeneration and Alzheimer's [20,27,28], these results are consistent with the role of phosphorylated Tau in HAND pathogenesis and suggest that increase in this factor may precede HAND diagnosis.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The above observations show that the tau protein may be at the intersection of many pathological mechanisms/processes/phenomena leading to severe neurodegenerative changes in the brain after ischemia. The facts show that an ischemic brain injury induces neuronal damage and death in the hippocampus via a tau protein-dependent mechanism, defining a new phenomenon that influences the long-term survival and/or death of post-ischemic neurons ( Table 2 , Figure 1 ) [ 33 , 34 , 41 , 42 , 49 , 60 , 63 , 64 , 67 , 68 , 149 , 150 , 151 ]. The underlying processes of neuronal death following ischemia include neuropathological effects in the tau protein.…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive evidence pointing to a close relationship between brain ischemia and AD [ 66 , 184 ]. Amyloid hypothesis assumes aberrant upregulation of Aβ production and/or its reduced clearance, which results in its accumulation in the brain.…”
Section: Discussionmentioning
confidence: 99%